2014
DOI: 10.1007/s12522-014-0193-1
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal therapy for non‐obstructive azoospermia: basic and clinical perspectives

Abstract: Microdissection testicular sperm extraction (micro-TESE) combined with intracytoplasmic sperm injection is a standard therapeutic option for patients with non-obstructive azoospermia (NOA). Hormonal treatment has been believed to be ineffective for NOA because of high gonadotropin levels; however, several studies have stimulated spermatogenesis before or after micro-TESE by using anti-estrogens, aromatase inhibitors, and gonadotropins. These results remain controversial; however, it is obvious that some of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 82 publications
0
15
0
1
Order By: Relevance
“…However, the sperm retrieval rate by micro-TESE, ranging between 20 and 60 % [1][2][3][4], remains unsatisfactory considering the negative physical, emotional, and financial effects of this procedure. Although a new attempt that could improve the chance of successful retrieval by micro-TESE such as hormonal therapy for NOA [12] is desirable, there is no generally accepted method that could drastically improve the success rate of micro-TESE at this moment. Therefore, there is also a pressing need for a reliable marker that will help guide physicians to determine cases for which micro-TESE would be suitable.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sperm retrieval rate by micro-TESE, ranging between 20 and 60 % [1][2][3][4], remains unsatisfactory considering the negative physical, emotional, and financial effects of this procedure. Although a new attempt that could improve the chance of successful retrieval by micro-TESE such as hormonal therapy for NOA [12] is desirable, there is no generally accepted method that could drastically improve the success rate of micro-TESE at this moment. Therefore, there is also a pressing need for a reliable marker that will help guide physicians to determine cases for which micro-TESE would be suitable.…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal treatments for NOA are considered to be ineffective because of high gonadotropin levels; however, previous studies reported that anti-estrogens, aromatase inhibitors, and gonadotropins stimulated spermatogenesis [81]. Ramasamy et al administered a pretreatment with aromatase inhibitors for patients with Klinefelter's syndrome whose serum testosterone levels were less than 300 ng/dl prior to micro-TESE.…”
Section: Hormonal Therapy Before or After Tesementioning
confidence: 99%
“…The administration of gonadotropins to men with NOA is a more comprehensive therapy typically used in combination with hCG and recombinant FSH [81]. Shiraishi et al reviewed 48 men with NOA who had negative sperm retrieval results by micro-TESE.…”
Section: Hormonal Therapy Before or After Tesementioning
confidence: 99%
“…The pathophysiology of NOA is heterogeneous and some, but not all, patients respond to hormonal therapy including anti-estrogens, aromatase inhibitors and gonadotropins. Such immature germ cells can potentially be further developed as represented by late MA or hypospermatogenesis histology [3]. is secreted rhythmically under the regulation of GnRH and the central nervous system.…”
mentioning
confidence: 99%